Improving accessibility and security on document management system: A Malaysian case study. Issue 1 (13th April 2018) - Abidin, Siti Salbiah Zainal; Husin, Mohd Heikal
Abstract : Document management system is an essential approach that should be managed well to ensure an effective and faster overall working process in an organization. Hardcopy documents has been one of the items that most organizations need to manage in a safe and secure manner due to the high dependency on most of their working procedure especially in government organizations. Hence, we proposed a new framework to improve the weaknesses of the existing document management procedures in government organizations. Our proposed framework integrates the implementation of an NFC system in this research due to its secure short - range communication, and the peer-to-peer communication capability in most mobile devices. Besides that, most existing government organizations within Malaysia could easily implement such technology for their internal usage as this technology is cost effective due to its availability on existing mobile devices on most Android based devices.